Ecological Efficiency of Some Hydrogen Production Processes - Braga, Lúcia Bollini [UNESP]; Tuna, Celso Eduardo [UNESP]; De Araujo, Fernando Henrique Mayworm [UNESP]; Vane, Lucas Fachini [UNESP]; Pedroso, Daniel Travieso [UNESP]; Silveira, José Luz [UNESP] (Springer Nature, 2017)
As hydrogen production is not a clean process in its separation (from acid, methane, hydroxide, water, alcohol, etc.), there are energy requirements, thus resulting in pollutant emissions along its production process. The pollutant emissions associated with the studied processes are presented and the equivalent carbon dioxide [(CO2)e], pollutant indicator (П g) and ecological efficiency (ε) of hydrogen production processes are determined. Moreover, for the processes using renewable energy sources, such as in the case of ethanol, biogas and green algae, carbon credit incorporation is also presented so as to make ecological efficiency values yet to be determined more realistic.